PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM KONTRAK BISNIS JUAL BELI DI MASA PANDEMI COVID-19 (Lex Jurnalica, 2020)
The Covid-19 pandemic was declared a national disaster by the government. Covid-19 pandemic has an impact on slowing economic growth so that it will result in the fulfillment of the achievements of the sale and purchase business contracts carried out by the parties. The purpose of this study is to analyze the legal protection of the parties involved in the sale and purchase business contract during the Covid-19 pandemic. This type of research is normative juridical. Data in the form of secondary data and data analyzed descriptively. The conclusion obtained is that it is not easy to determine whether the obligations which are not carried out in a business purchase contract are a result of the Covid-19 pandemic. Conditions that can be categorized as Force Majeure in a sale and purchase contract such as a policy of limiting access to an area by the government that causes goods can not be sent according to the agreed schedule, especially for export and import goods that require conditions. Related government policies that result in late delivery of goods in the sale and purchase meet the elements in force majeure which are not fulfilled due to events that prevent debtors from performing and the event cannot be known or is expected to occur when making an agreement. The debtor is not charged to bear compensation, fines. It is necessary for the parties' discretion to negotiate business contracts carried out such as rearrangement of fulfillment of the achievements set forth in the sale and purchase business contract.Keywords: Legal Protection, Business Contracts, Sale and Purchase, Pandemic Covid-19Â